The symplectic geometry of higher Auslander algebras: Symmetric products of disks - Dyckerhoff, Tobias; Jasso, Gustavo; Lekili, Yankι (Forum of mathematics. Sigma, 2021)
We show that the perfect derived categories of Iyama’s d -dimensional Auslander algebras of type ${\mathbb {A}}$ are equivalent to the partially wrapped Fukaya categories of the d -fold symmetric product of the $2$ -dimensional unit disk with finitely many stops on its boundary. Furthermore, we observe that Koszul duality provides an equivalence between the partially wrapped Fukaya categories associated to the d -fold symmetric product of the disk and those of its $(n-d)$ -fold symmetric product; this observation leads to a symplectic proof of a theorem of Beckert concerning the derived Morita equivalence between the corresponding higher Auslander algebras of type ${\mathbb {A}}$ . As a by-product of our results, we deduce that the partially wrapped Fukaya categories associated to the d -fold symmetric product of the disk organise into a paracyclic object equivalent to the d -dimensional Waldhausen $\text {S}_{\bullet }$ -construction, a simplicial space whose geometric realisation provides the d -fold delooping of the connective algebraic K -theory space of the ring of coefficients.